Manganese Removal Using Functionalised Thiosalicylate-Based Ionic Liquid: Water Filtration System Application - Ain Aqilah Basirun; Wan Azlina Wan Ab Karim; Ng Cheah Wei; Jiquan Wu; Cecilia Devi Wilfred (Molecules, 2023)
Aiming at the generation of new functionalised thiosalicylate-based ionic liquids, a polymeric hydrogel consisting of 1-hexylimidazole propionitrile thiosalicylate [HIMP][TS], with a solid biomaterial support based on polyvinyl alcohol (PVA)–alginate beads, was produced. This study aimed to develop a treatment method for removing manganese (Mn) heavy metal from industrial wastewater, which is known to be toxic and harmful towards the environment and human health. The method utilised an adsorption-based approach with an alginate adsorbent that incorporated a functionalised thiosalicylate-based ionic liquid. The synthesised smooth round beads of PVA–alginate–[HIMP][TS] adsorbent were structurally characterised using Fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FESEM). The Mn concentration and removal efficiency were evaluated using atomic absorption spectroscopy (AAS). Three important parameters were evaluated: pH, adsorbent dosage, and contact time. During optimisation using the interactive factor design of experiments through the Box–Behnken model, the results showed that the system achieved a maximum Mn removal efficiency of 98.91% at an initial pH of 7.15, with a contact time of 60 min, using a bead dosage of 38.26 g/L. The beads were also tested in an available water filtration prototype system to illustrate their industrial application, and the performance showed a removal efficiency of 99.14% with 0 NTU total suspended solid (TSS) and 0.13 mg/L turbidity analysis. The recyclability of PVA–alginate–[HIMP][TS] beads using 0.5 M HCl resulted in four cycles with constant 99% Mn removal. The adsorption capacity of Mn was also determined in optimum conditions with 56 mg/g. Therefore, the alginate–thiosalicylate-based ionic liquid system is considered an effective and environmentally friendly method for removing Mn heavy metal due to the high removal efficiency achieved.